DR5‐Cbl‐b/c‐Cbl‐TRAF2 complex inhibits TRAIL‐induced apoptosis by promoting TRAF2‐mediated polyubiquitination of caspase‐8 in gastric cancer cells. Issue 12 (27th October 2017) - Xu, Ling; Zhang, Ye; Qu, Xiujuan; Che, Xiaofang; Guo, Tianshu; Li, Ce; Ma, Rui; Fan, Yibo; Ma, Yanju; Hou, Kezuo; Li, Danni; Hu, Xuejun; et al.
Abstract : Ubiquitination of caspase‐8 regulates TNF‐related apoptosis‐inducing ligand (TRAIL) sensitivity in cancer cells, and the preligand assembly complex plays a role in caspase‐8 polyubiquitination. However, whether such a complex exists in gastric cancer cells and its role in TRAIL‐triggered apoptosis is unclear. In this study, DR5, casitas B‐lineage lymphoma‐b (Cbl‐b)/c‐Cbl, and TRAF2 formed a complex in TRAIL‐resistant gastric cancer cells, and Cbl‐b and c‐Cbl were the critical adaptors linking DR5 and TRAF2. Treatment with TRAIL induced caspase‐8 translocation into the DR5‐Cbl‐b/c‐Cbl‐TRAF2 complex to interact with TRAF2, which then mediated the K48‐linked polyubiquitination of caspase‐8. The proteasome inhibitor bortezomib markedly enriched the p43/41 products of caspase‐8 activated by TRAIL, indicating proteasomal degradation of caspase‐8. Moreover, TRAF2 knockdown prevented the polyubiquitination of caspase‐8 and thus increased TRAIL sensitivity. In addition, the inhibition of Cbl‐b or c‐Cbl expression and overexpression of miR‐141 targeting Cbl‐b and c‐Cbl partially reversed TRAIL resistance by inhibiting the interaction between TRAF2 and caspase‐8 and the subsequent polyubiquitination of caspase‐8. These results indicate that the DR5‐Cbl‐b/c‐Cbl‐TRAF2 complex inhibited TRAIL‐induced apoptosis by promoting TRAF2‐mediated polyubiquitination of caspase‐8 in gastric cancer cells. Abstract : Targeting TNF‐related apoptosis‐inducing ligand (TRAIL) receptors holds promise for selective induction of apoptosis in cancer cells. Here, results show that DR5, casitas B‐lineage lymphoma‐b (Cbl‐b)/c‐Cbl, and tumor necrosis factor receptor‐associated factor 2 (TRAF2) form a complex in TRAIL‐resistant gastric cancer cells (Cbl‐b and c‐Cbl are critical adaptors linking DR5 and TRAF2). TRAIL treatment induced caspase‐8 translocation into the DR5‐Cbl‐b/c‐Cbl‐TRAF2 complex to interact with TRAF2, consequently mediating the K48‐linked polyubiquitination of caspase‐8. Inhibition of Cbl‐b/c‐Cbl expression and overexpression of miR‐141 targeting Cbl‐b and c‐Cbl partially reversed TRAIL resistance by inhibiting the interaction between TRAF2 and caspase‐8 and the subsequent polyubiquitination of caspase‐8.